The effect of changing movement and posture using motion-sensor biofeedback, versus guidelines-based care, on the clinical outcomes of people with sub-acute or chronic low back pain-a multicentre, cluster-randomised, placebo-controlled, pilot trial - Kent, Peter; Laird, R.; Haines, T. (Biomed Central Ltd, 2015)
Background: The aims of this pilot trial were to (i) test the hypothesis that modifying patterns of painful lumbo-pelvic movement using motion-sensor biofeedback in people with low back pain would lead to reduced pain and activity limitation compared with guidelines-based care, and (ii) facilitate sample size calculations for a fully powered trial. Methods: A multicentre (8 clinics), cluster-randomised, placebo-controlled pilot trial compared two groups of pati ents seeking medical or physiotherapy primary care for sub-acute and chronic back pain. It was powered for longitudinal analysis, but not for adjusted single-time point comparisons. The intervention group (n?=?58) received modification of movement patterns augmented by motion-sensor movement biofeedback (ViMove, dorsaVi.com) plus guidelines-based medical or physiotherapy care. The control group (n?=?54) received a placebo (wearing the motion-sensors without biofeedback) plus guidelines-based medical or physiotherapy care. Primary outcomes were self-reported pain intensity (VAS) and activity limitation (Roland Morris Disability Questionnaire (RMDQ), Patient Specific Functional Scale (PSFS)), all on 0-100 scales. Both groups received 6-8 treatment sessions. Outcomes were measured seven times during 10-weeks of treatment and at 12, 26 and 52 week follow-up, with 17.0 % dropout. Patients were not informed of group allocation or the study hypothesis. Results: Across one-year, there were significant between-group differences favouring the intervention group [generalized linear model coefficient (95 % CI): group effect RMDQ -7.1 (95 % CI-12.6;-1.6), PSFS -10.3 (-16.6; -3.9), QVAS -7.7 (-13.0; -2.4); and group by time effect differences (per 100 days) RMDQ -3.5 (-5.2; -2.2), PSFS -4.7 (-7.0; -2.5), QVAS -4.8 (-6.1; -3.5)], all p? < ?0.001. Risk ratios between groups of probability of improving by > 30 % at 12-months?=?RMDQ 2.4 (95 % CI 1.5; 4.1), PSFS 2.5 (1.5; 4.0), QVAS 3.3 (1.8; 5.9). The only device-related side-effects involved transient skin irritation from tape used to mount motion sensors. Conclusions: Individualised movement retraining using motion-sensor biofeedback resulted in significant and sustained improvements in pain and activity limitation that persisted after treatment finished. This pilot trial also refined the procedures and sample size requirements for a fully powered RCT. This trial (Australian New Zealand Clinical Trials Registry NCT01572779) was equally funded by dorsaVi P/L and the Victorian State Government.